2017
DOI: 10.1016/j.ecolmodel.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

A coffee agroecosystem model: III. Parasitoids of the coffee berry borer ( Hypothenemus hampei )

Abstract: a b s t r a c tParasitoids native to tropical Africa have been released in the Americas for the biological control of the coffee berry borer (CBB), but their establishment has been checkered. A tritrophic distributed maturation time model for the coffee plant -CBB -three parasitoids (Phymastichus coffea, Cephalonomia stephanoderis, Prorops nasuta) system was proposed by Gutierrez et al. (1998). Based on this pioneering work, and improved models for coffee and CBB (Rodríguez et al., 2011(Rodríguez et al., , 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 52 publications
0
16
0
7
Order By: Relevance
“…They concluded that only P. coffea has the demographic characteristics to regulate CBB populations. Rodriguez et al (2013, 2017) updated the coffee–CBB–parasitoids relationship simulation model developed by Gutierrez et al (1998) and concluded that control of CBB by augmentative releases of parasitoids in the Americas is neither effective nor stable and the introduction of additional bethylids will be detrimental. They suggested that P. coffea could provide substantial but insufficient control in zones with narrow flowering periods that concentrate the harvest periods including Londrina, PR and Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that only P. coffea has the demographic characteristics to regulate CBB populations. Rodriguez et al (2013, 2017) updated the coffee–CBB–parasitoids relationship simulation model developed by Gutierrez et al (1998) and concluded that control of CBB by augmentative releases of parasitoids in the Americas is neither effective nor stable and the introduction of additional bethylids will be detrimental. They suggested that P. coffea could provide substantial but insufficient control in zones with narrow flowering periods that concentrate the harvest periods including Londrina, PR and Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…An early multitrophic study of the coffee agroecosystem using the mechanistic physiologically based demographic modeling (PBDM) approach 19 , 20 demonstrated that CBB parasitoids alone were not efficient in controlling CBB 21 . Those findings were confirmed in subsequent restudy of the coffee system using PBDMs that introduced extensive new data from Colombia on the dynamics of coffee growth and development 22 24 , the effects of solar radiation on floral bud initiation; effects of leaf water potential on breaking dormancy in flower buds; effects of low temperature on photosynthesis and defoliation; enhanced CBB biology and population dynamics including the effects of intraspecific competition, temperature and rainfall on CBB adult emergence; the impact of baited traps for CBB control; and refinements of parasitoid biology and interactions (i.e. intra and inter competition).…”
Section: Introductionmentioning
confidence: 67%
“…Results of Rodríguez et al . 24 show that C. hyalinipennis , interacts negatively with the other betilids and provides poor control of CBB, and this argues against its introduction, and hence was not considered here. The present work explores only the performance of C. stephanoderis , P. nasuta and P. coffea .…”
Section: Control Componentsmentioning
confidence: 99%
See 2 more Smart Citations